Proposição de framework para projeto, planejamento e gestão de transporte sustentável: revisão sistemática da literatura e análise de especialistas - Oliveira, Gerson Barbosa Matzembacker (2019)
Road transport is a determining function in the context of the contemporary economy and society. Being that it is one of the activities that generates more CO2 emissions. It is therefore important that the road transport project has been alternated from urban and suburban areas. With this, the work consists in the proposal of an integrated solution for the design, planning and management of sustainable road transport. The research method adopted was the bibliographical and systematic review of the literature with the evaluation of ten years through the questionnaire and the version as the use of design guidelines, planning and statistics management. With this function, some factors such as the routing and the location of the transport will be fundamental for the reduction of costs and the optimization of the operation in the time and quality of the service provided. This is the presentation of the presentation of the document, the development and management of the concomitant solid vehicle. Therefore, the results of its main proposition tools are ancillary in the calculation of companies and investment managers in the preparation of assertive steps within a planned chronology and budget.